Chronic facial pain: a multidisciplinary problem. Issue 6 (1st December 2001) - Madland, G; Feinmann, C
Abstract : Atypical facial pain is an unrecognised and unhelpful diagnosis but one which describes chronic pains that do not fit the present classification system. Due to the site of the pain, patients may seek and, indeed, receive treatment from dental practitioners and specialists, but the pain is often unresponsive and may have more in common with unexplained medical symptoms affecting other areas of the body, than with other dental symptoms. This review suggests a need for a diagnostic category of "chronic facial pain", which demands a multidisciplinary approach to diagnosis and management.